Avaliação da eficiência de processos avançados na remoção de toxicidade de lixiviado de aterro sanitário - Beatriz Gasparini Reis (2014)
The complex composition and recalcitrant nature of the leachate, enhanced with aging landfills and also added to stricter standards for its disposal, represents a huge obstacle to barrier for the conventional treatment, that are no more effective on leachate treatment. MBR came as a promising alternative as they are compact and modular systems and represent a more efficient system of degradation. But due to limitations of bacteria sludge on degrading leachates refractory compounds, yeasts and fungi has been used instead of bacteria. AOP are also a promising technique as it is capable of oxidizing compounds that biological treatment are not. NF is a very effective technique generally used on effluent polishing and it can drastically improve effluent quality. Toxicity is an important tool as it´s consequence of the interaction of different pollutants presents on the leachate, its synergic and antagonist effects and different physicochemical properties, providing then much more information on the quality of leachate than physicochemical analyses alone. In this study, leachate of a 5 years old landfill of Minas Gerais (Brazil) was submitted to three different routes using MBR, yeast MBR (YMBR) and Fenton-microfiltration (FMF). Both MBR routes have an air-stripping stage before the MBR and all routes have a final polishing stage using NF membrane. Performances were evaluated, using physicochemical analyses and toxicity tests. All routes showed high removal rates. When compared individually, YMBR route has shown high removal efficiency than the MBR route for most of the parameters analyzes, but similar performance to FMF route. Both bioreactors routes showed an increase of nitrites and nitrates. For toxicity, only MBR and FMF routes were capable of achieving complete removal of toxicity. The YMBR route showed a final effluent with high toxicity and physicochemical analyzes do not explain these results. The identification of compounds shows that there is a wide range of compounds in the raw leachate and still others are produced in the secondary treatment steps. The toxicity of these compounds alone do not explain the results, but the resulting effects of the interactions between them may further elucidate the true causes of toxicity. Thus, we emphasize the importance of toxicity testing in the evaluation of effluent treatment. Toxicity does not always follow the same pattern of removal of physical and chemical parameters. Treatment strategies should not only be effective in achieving the physico-chemical standards required but removal of toxicity as well.